2015
DOI: 10.1166/jnn.2015.9481
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Traditional Nanophytomedicines for Clinical Treatment: Manufacturing Processes and Nonlinear Response Patterns

Abstract: The purpose of the present paper is to (a) summarize evidence for the nanoparticle nature and biological effects of traditional homeopathically-prepared medicines at low and ultralow doses; (b) provide details of historically-based homeopathic green manufacturing materials and methods, relating them to top-down mechanical attrition and plant-based biosynthetic processes in modern nanotechnology; (c) outline the potential roles of nonlinear dose-responses and dynamical interactions with complex adaptive systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The increase of cell viability at concentration up to 1600  μ g/mL could be explained by the nonlinear dose-responses of plants and other natural products [40]. Gan et al [41] demonstrated that 10 mg/kg dose of Chinese LBBs was more effective than 5 and 20 mg/kg doses in the reduction of sarcoma weight and in improving the immune system in the mice.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of cell viability at concentration up to 1600  μ g/mL could be explained by the nonlinear dose-responses of plants and other natural products [40]. Gan et al [41] demonstrated that 10 mg/kg dose of Chinese LBBs was more effective than 5 and 20 mg/kg doses in the reduction of sarcoma weight and in improving the immune system in the mice.…”
Section: Resultsmentioning
confidence: 99%
“…So natural products have been utilized as complementary medicine or preventive medicine. Recently, it was reported that nanoscale natural products are prospects for homeopathic medicine [69,[78][79][80]. Chrysin is also a good candidate for homeopathic medicine.…”
Section: Improvement Strategies For Chrysinmentioning
confidence: 99%
“…Clearly homeopathic manufacturing is 'green' in that the reagents are natural materials rather than synthetic chemicals that can leave trace toxic adsorbants on the NP surfaces. 88 A common method for less toxic nanotechnology manufacturing of nanoparticles is to apply ultrasound or sonication as the means of agitating a given solution. 86 A variant of this mechanical method with soluble source materials such as sodium chloride (cf., Natrum muriaticum) or potassium iodide (cf., Kalium iodatum) involves intense agitation of a solute-solvent solution with ultrasound to concomitantly generate source nanoparticles and embed them into the walls of the glassware container.…”
Section: Figure 2 Top Down and Bottom Up Manufacturing Strategies Formentioning
confidence: 99%